Narrativas de escolarização: experiências familiares e escolares de uma jovem transexual - SILVA, Joicy Cardoso da (2021)
This work, entitled “school narratives: family and school experiences of a transexual youth”, sought to answer the following questions: How did the process of transsexual experience take place in the family context during the childhood and adolescence of the young trans? And what were the experiences lived by the trans student during her schooling process? Thus, the objective was to raise reflections on the experiences lived from childhood to adolescence of the young transsexual, highlighting the family and school context. To provide referral, the post-critical approach and discourse analysis was chosen as a methodology to support this research, using as a data collection instrument the semi-structured narrative interview technique that was performed from the narratives of the young transgender Evelyn Sofhia, who at birth was designated male as male, but identifies and considers herself a woman. The research has as theoretical reference; Scott (1995), Louro (1997), Bento (2008), Foucault (1988), Coutinho Jorge and Travassos (2018). The results show that it is necessary to broaden the debate on the theme addressed here, transsexuality. From the analysis of the interviewee's narratives, it is clear that it is still necessary to fight and resist before a society that mostly practices physical and psychological violence against people who do not identify with the gender attributed at birth. According to the student's narratives, it was noted that both the school community, the family and society need training as well as gender and sexuality issues, as well as reflections on transsexual identity. This discussion becomes necessary in view of the numerous difficulties in recognizing transsexual identity in the face of this standardized, heteronormative system and historically pre-established relations of domination.